Needs Analysis of Fintech in Financial Services toward Industry-4.0 Era in Indonesia - Henricus Bambang Triantono; Aryusmar Aryusmar (AIBPM Publisher, 2019)
This paper presents the needs analysis of fintech whose existence has changed the payment system in society. This research method is descriptive analytic to emphasize the aspect of indepth understanding of the problems. The purpose and benefits are to examine the dynamics of the development of fintech needs in Indonesia. This study found that fintech in Indonesia has grown in various sectors, such as start-up, lending, personal finance, and retail investment. Finally, that the needs of fintech in Financial Services should be supported by regulations and internet infrastructure, to make it more developed financial transactions toward Industry-4.0.